(untitled) (International Seven Journal of Multidisciplinary, 2025)
Breast cancer is one of the leading causes of female mortality worldwide, due to late detection and limited access to diagnostic methods. This article reviews the feasibility of using volatile organic compounds (VOCs) present in exhaled breath as a complementary diagnostic tool through the use of electronic noses. These noninvasive technologies can detect specific chemical patterns related to metabolic alterations associated with cancer and could be integrated into current screening systems. The review covers recent studies that use techniques such as mass spectrometry and chemical sensors to identify VOC profiles characteristic of breast cancer. Compounds such as 2-propanol, heptanal, and cyclopentanone are highlighted, which demonstrate high sensitivity and specificity in differentiating between healthy and diseased patients. The metabolic pathways involved and the biological effects of different chemical groups are also explored. Although electronic nose technology still faces technical and standardization challenges, its advantages—such as speed, low cost, and ease of use—make it a promising alternative for improving early diagnosis and personalized medicine in oncology. It is concluded that further research is needed to validate its clinical applicability.